Comparing "Individual Health" Message Framing to "Organizational Efficiency" Message Framing to Encourage Adoption of Wearable Health Technologies at Work. Issue 2 (February 2021) - Kwong, Jillian K.; Cruz, Ignacio; Murphy, Sheila T.
Purpose: To determine the relative impact of framing on employee intention to adopt wearable technology (eg, Fitbits) at work. Setting and Design: Posttest only online experiment utilizing a 2 (framing: organizational efficiency vs individual health) × 2 (financial incentive: absent vs present) between-subjects design. Participants: Participants (N = 310) were 18 years or older, currently employed, and residing in the United States. Measures: Unified Theory of Acceptance and Use of Technology (UTAUT) subscale on behavioral intent (modified for wearable technology). Analysis: Chi-square and between-subjects analysis of variance. Results: Participants receiving the organizational efficiency frame ( M = 3.97) expressed significantly lower intention to adopt a wearable compared to the individual health frame ( M = 4.37), F 2, 308 = 3.99, P = .047. Financial incentives had a positive effect on adoption intention ( M = 4.39 with incentive, M = 3.95 no incentive), F 2, 308 = 4.46, P = .036. The main effects of frame and incentive were additive, with participants in the individual health with incentive condition (n = 78, M = 4.60) expressing the highest intention to adopt and organizational efficiency without incentive expressing the lowest adoption intention (n = 77, M = 3.80; P = .03). Conclusions: Messaging emphasizing individual health benefits plus financial incentives might prove most successful when encouraging adoption of wearables at work.